Importance of Self-Efficacy in Overcoming Quarter-Life Crisis among Fresh Graduates - Laurenza, Hana; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Individuals who have just completed their studies at the university, commonly referred to as fresh graduates, will inevitably undergo a transition period from adolescence to adulthood known as the quarter life crisis. To face this crisis, there is a need for confidence to be able to confront every problem that arises, this confidence is referred to as self-efficacy. This study aims to examine whether there is a relationship between self-efficacy and the quarter-life crisis. The research was conducted using a quantitative approach with correlation analysis. The research subjects were fresh graduates who had graduated from college 2 years and were aged 21-25 years. The sampling technique used was accidental sampling. The self-efficacy scale used the General Self-Efficacy Scale 12 (GSES-12) (α = 0.858), while the quarter-life crisis scale used was the Developmental Crisis Questionnaire (DCQ-12) (α = 0.832). Data collection was done using questionnaires distributed online through social media. The results of this study indicate that self-efficacy has a significant relationship with the quarter-life crisis at 0.000 (p<0.05), with a correlation coefficient of -0.635, indicating that self-efficacy is negatively correlated with the quarter-life crisis. In other words, the higher the level of self-efficacy, the lower the level of quarter life crisis.Individu yang baru saja menyelesaikan studi di perguruan tinggi, atau sering disebut sebagai fresh graduate, tentunya akan melewati masa transisi dari remaja menuju dewasa yang dikenal dengan quarter life crisis. Untuk menghadapi krisis tersebut perlunya keyakinan agar mampu menghadapi tiap masalah yang datang, keyakinan itu disebut dengan efikasi diri. Penelitian ini bertujuan untuk melihat apakah terdapat hubungan antara efikasi diri dengan quarter life crisis. Penelitian dilakukan dengan pendekatan kuantitatif dengan analisis korelasi. Subjek penelitian merupakan fresh graduate yang telah lulus kuliah terhitung 2 tahun setelah kelulusan, serta berusia 21-25 tahun. Teknik pengambilan sampel menggunakan accidental sampling. Skala efikasi diri menggunakan General Self-Efficacy Scale 12 (GSES-12) (α = 0,858), sedangkan skala quarter life crisis yang digunakan adalah Developmental Crisis Questionnaire (DCQ-12) (α = 0,832). Pengumpulan data menggunakan kuesioner yang dibagikan secara online melalui media sosial. Hasil dari penelitian ini menunjukkan bahwa efikasi diri memiliki hubungan yang signifikan terhadap quarter life crisis sebesar 0,000 (p<0,05), dengan koefisien korelasi sebesar -0,635 hal ini menunjukkan efikasi diri berhubungan negatif dengan quarter life crisis. Artinya semakin tinggi tingkat efikasi diri maka semakin rendah tingkat quarter life crisis.